Learning Support for Mature Students. - Hoult, E. (Sage study skills., 2006)
Written from a teacher's viewpoint and based on the author's experiences during a long career of working with adult students, this book explores how adults learn and the ways in which different abilities and experiences can be used to learn more effectively. Key features include: -nine chapters each dealing with a different aspect of learning -models and concepts of learning developed and adapted from a range of sources from the disciplines of education and psychology -suggestions for further reading at the end of each chapter -individual self-assessment exercises to help gain a detailed under.